Polyurethane Based Anti-Graffiti Coatings - Anand S. Khanna; Priyanka Adapala (Research Highlights in Science and Technology Vol. 2, 2023)
Anti-graffiti coatings were synthesized from polyurethane with varying concentration of silicon modified polyacrylate with an - OH functional group. Various tests for evaluating the graffiti resistance of the coating included the measurements of contact angle of water drop on the sprayed coating, and visual evaluation of stain removal and measurements of colour change. It was shown that the best performance was achieved by 5 wt. % of Silicone polyacrylate in pristine PU which demonstrated 95% stain removal. Despite having low mechanical properties of these coatings, they demonstrated remarkable graffiti resistance. In order to improve the mechanical properties of the coatings, nano-particle inclusion was considered. For improving mechanical properties, such as surface hardness, elastic modulus, and scratch resistance, nano-silica particles were added. It was assured to have a coating with even distribution of nano-silica particles. A 5 wt% nano-silica particles were found to create such coating with composition PU-5 wt% silicone polyacrylate. Measurements of colour changes revealed that the inclusion of nanosilica particles had no impact on the material’s resistance to graffiti.